On the Brody hyperbolicity of the complex space C^3 avoiding complex and real hyperplanes - Jalled, Abdessami (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 We study the Brody hyperbolicity of а complex space C^3 avoiding the arrangement of complex and real hyperplanes in C^3. We also investigate the projection onto the projective complex space C P^2 of holomorphic maps fC→C^3 avoiding this configuration.